2016
DOI: 10.1556/018.67.2016.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of alginate lyase from locally isolated marinePseudomonas stutzeriMSEA04

Abstract: An alginate lyase with high specific enzyme activity was purified from Pseudomonas stutzeri MSEA04, isolated from marine brown algae. The alginate lyase was purified by precipitation with ammonium sulphate, acetone and ethanol individually. 70% ethanol fraction showed maximum specific activity (133.3 U/mg). This fraction was re-purified by anion exchange chromatography DEAE-Cellulose A-52. The loaded protein was separated into 3 peaks. The second protein peak was the major one which contained 48.2% of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…About 55.64 mg of the partially purified L-glutaminase was diluted in 10 ml of 0.1M phosphate buffer at pH 8.0 and purified using Sephadex G-100 gel column (1.6 cm × 50 cm). The elute was obtained at a rate of 0.5 ml/min adjusted with a peristaltic pump and collected in 5 ml (Beltagy et al, 2016;Farag et al, 2021). Protein content and L-glutaminase activity were assessed as previously mentioned.…”
Section: Purification Of L-glutaminasementioning
confidence: 99%
“…About 55.64 mg of the partially purified L-glutaminase was diluted in 10 ml of 0.1M phosphate buffer at pH 8.0 and purified using Sephadex G-100 gel column (1.6 cm × 50 cm). The elute was obtained at a rate of 0.5 ml/min adjusted with a peristaltic pump and collected in 5 ml (Beltagy et al, 2016;Farag et al, 2021). Protein content and L-glutaminase activity were assessed as previously mentioned.…”
Section: Purification Of L-glutaminasementioning
confidence: 99%
“…With the same buffer and a flow rate of 0.5 ml/min, the protein was eluted. The collected fractions of β-mannanase were pooled at 4°C, then protein content and β-mannanase activity were measured (Beltagy et al, 2016;Farag et al, 2018).…”
Section: Gel Filtration Chromatographymentioning
confidence: 99%
“…Kotil et al (20) found that the better temperature for alginate lyase generation from Pseudomonas aeruginosa AG LSL-11 was 30°C, with activity 0.355 U/ml. Beltagy et al (9), utilized sephadex G-100 in alginate lyase purification from Pseudomonas stutzeri MSEA04 with specific activity 116 U/mg U/mg and yield 48.2%. Table 2.…”
Section: Incubation Temperaturementioning
confidence: 99%